If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (U + -7) * 9 = 36 Reorder the terms: (-7 + U) * 9 = 36 Reorder the terms for easier multiplication: 9(-7 + U) = 36 (-7 * 9 + U * 9) = 36 (-63 + 9U) = 36 Solving -63 + 9U = 36 Solving for variable 'U'. Move all terms containing U to the left, all other terms to the right. Add '63' to each side of the equation. -63 + 63 + 9U = 36 + 63 Combine like terms: -63 + 63 = 0 0 + 9U = 36 + 63 9U = 36 + 63 Combine like terms: 36 + 63 = 99 9U = 99 Divide each side by '9'. U = 11 Simplifying U = 11
| 5x=(5-7(5-8x))/(8) | | 10(7m-6)=1+9m | | X^2-30+56=-25 | | 39*25= | | 3X/4=×^2/8 | | 3y=16-5y | | -2x+7=x-23 | | 1+2x+3x=16 | | -59-3n=-8(2-5n) | | (E+2)*2=14 | | 2x=(4-5(8-5x))/(7) | | 2x^2+20x=112 | | -44-10k=-6(10+x) | | 15x-2y=-16 | | 2x+5x-3x=8+2 | | n^2=40 | | (3x-2)=(6x+5) | | y^2(y^2-3y-1)=y | | -3k-8=k-5k | | 2/3x•10 | | y^2(y^2-3y-1)=x | | x+8=8-x | | -z^2-4x=-79 | | 3x+15=2x+11 | | Mgh=10m/s | | -1-4(x-6)=39-2x | | 3x+1/2=1 | | -3x^2+36x=81 | | 15x^2-54x+27=0 | | -63=7c | | 6sinx+5=0 | | -15+3a-7-6=8-3a |